Caracterização bromatológica da polpa desidratada de frutos de Euterpe edulis Mart. e seleção de genótipos - Dias, Natália Caroliny da Silva (2017)
The species Euterpe edulis Martius is characterized by producing a high quantity of fruits that serve as food for birds and mammals during long periods of scarce resources. However, it's estimated that losses are occurring in the diversity of the species due to the forest fragmentation and the intense extractivism of the palm heart produced from the colonization of the country until the present day. Currently, the species is on the list of endangered species. The objective of this work was to chemically characterize the dehydrated pulp of the fruits of 60 E. edulis accessions collected in the southern region of Espírito Santo; evaluate the genetic variability and select genotypes based on chemical characters related to the commercialization of the fruits in order to apply them to the breeding program of the species. Fruits were collected from 60 accessions and analyzed for the following characteristics: moisture, biomass, yield, total acidity (ATT), total soluble solids (TSS), fiber (FIB), lipids (LIP), pH, mineral content (CM), total phenolic compounds (FNT), total anthocyanins (ANT), total flavonols (FLV); protein (PROT); total soluble sugars (AT) and soluble reducing sugars (AR). The Scott-Knott grouping test was performed at 5% probability. For the analysis of the genetic variability between and among the accessions was used.the method of grouping between groups (UPGMA) and analysis of molecular variance (AMOVA). The selection index was based on mixed models (REM/BLUP) and the mean rank of Mulamba and Mock. The E.edulis plant materials from southern Espírito Santo showed considerable variation in chemical contents with divergent access within the same locality. The UPGMA group structured the 60 accesses into four groups by the significance obtained by the Mojena method (1977). The genetic distance between the accessions of groups I and II was low indicating high similarity between them. The groups III and IV showed only one access, which diverged from all others. AMOVA was not significant. The accesses that obtained the best predicted gains according to the selection indices were IB3P4, IB3P9, IB3P5, IB3P6 and IB3P1, being able to occupy position of base individuals for crossing in the breeding program of the species.